REFLECTIVE LEARNING IN SOCIAL WORK EDUCATION IN THE FIELD OF SUBSTANCE ABUSE - Slabbert, Ilze (Social Work/Maatskaplike Werk, 2016)
Reflective learning is very much part of social work education. A qualitative study was proposed with final-year social work students at a selected university in South Africa doing a course in the field of substance abuse. The participants completed a reflective exercise on abstaining from an aspect/habit/substance in their own lives for three weeks. Six themes emerged, namely abstinence from: depressants, stimulants, opioids, food, social media and bad habits. Findings indicated that students gained an insight into possible harmful patterns in their own lives as well as into the complexity of life-long abstinence in prospective clients’ lives. Recommendations are provided for social work education, practice and research.